The Effectiveness of Lecture and Demonstration Methods in Improving the Communication Skills of Students in the Mandarin Language Program at Prima Indonesia University - Sutana, Jocelyn; Wenny,; Lisa, Mei; Paulia, (Jurnal Indonesia Sosial Sains, 2026)
Mandarin communication skills are important for students in the Mandarin Language Study Program at Prima Indonesia University; however, there are obstacles related to pronunciation, sentence structure, and self-confidence, so effective teaching methods are needed. This study aims to assess the influence of lecture and demonstration approaches on the communication abilities of students in the Mandarin Language Study Program at Prima Indonesia University. This study employed a quantitative method using 36 students as respondents. Data collection was conducted by distributing surveys via Google Forms. Coefficients of determination, F-tests, t-tests, validity and reliability tests, and classical assumption tests were used to analyze the data. The findings demonstrated that students' communication abilities were not significantly affected by the lecture method. On the other hand, the demonstration method was shown to significantly and positively improve students' communication abilities. Therefore, it can be concluded that, in helping students in the Mandarin Language Study Program at Prima Indonesia University improve their communication abilities, the demonstration method is more effective than the lecture method.